The Effect of Service Quality and Supply Chain Agility on Customer Satisfaction Mediated by Customer Trust - Kasih, Agatha Febrina; Ardyan, Elia (Jurnal Entrepreneur dan Entrepreneurship, 2025)
The aim of this study is to examine how supply chain agility and service quality affect customer happiness, with customer trust serving as a mediating factor. This method of this study is a quantitative research methodology. A total of 266 valid replies were gathered from the online questionnaire and offline paper-based surveys used to collect the data. SEM-PLS was used to evaluate the data. The results show that customer satisfaction is positively impacted by customer trust, service quality has a direct impact on customer satisfaction, supply chain agility has an impact on customer satisfaction, and service quality positively influences customer trust.